Dual Biologic Therapy for Psoriasis in a Patient with Atopic Dermatitis - Ma L; Chen X; Aziz MAA; Chen A; Cai T; Chen S (Psoriasis: Targets and Therapy)
Ling Ma, Xiaoli Chen, Mohammed Ali Ali Aziz, Aijun Chen, Tao Cai, Shuang Chen Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Tao Cai, Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, People’s Republic of China, Email 15902305525@163.com Shuang Chen, Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, People’s Republic of China, Email shuangchen07@hotmail.comAbstract: Psoriasis and atopic dermatitis (AD), once viewed as mutually exclusive diseases, are increasingly recognized to co-occur in complex inflammatory phenotypes. We present a 17-year-old male with multimorbid atopic conditions, including persistent atopic dermatitis, allergic rhinitis, and asthma, who developed new-onset psoriasis in the absence of previous biologic therapy. Initially misdiagnosed as exacerbated AD, he received ineffective treatment for one year. Treatment with secukinumab yielded limited improvement in psoriatic symptoms and eczematous lesions. AD and psoriasis significantly improved after adding dupilumab for 12 weeks; there were no documented side effects and a durable remission lasting 78 weeks. This case report underscores the importance of vigilance in patients with long-standing AD for newly emerging psoriasis and cautions against attributing all new rashes solely to chronic AD history. This case highlights the potential benefit of dual biologic therapy in managing concurrent type 2 inflammatory diseases and psoriasis, suggesting that a comprehensive immune-modulatory approach may be advantageous for patients with these coexisting conditions.Keywords: dupilumab, secukinumab, psoriasis, atopic dermatitis, dual biologic therapy